Bioactive constituents from Medicago sativa L. with antioxidant, neuroprotective and acetylcholinesterase inhibitory activities. (June 2018) - Liu, Xue-Gui; Huang, Ming-Yuan; Gao, Pin-Yi; Liu, Chang-Feng; Sun, Yu-Qiu; Lv, Meng-Chao; Yao, Guo-Dong; Zhang, Li-Xin; Li, Dan-Qi
Highlights: Four new isoflavane glycosides (1 –4 ) and seven known compounds (5 –11 ) were isolated from M. sativa . The absolute configurations of the new isoflavane glycosides were determined for the first time. Antioxidant, AChE inhibitory and neuroprotective activities of all the isolated compounds were studied. Abstract: Medicago sativa L. is an important source of functional foods and supplements, which can improve human health. The present work was carried out to search for potential antioxidants from M. sativa to treat neurodegeneration. Four new isoflavane glycosides (1 –4 ) were isolated from M. sativa, along with seven known compounds (5 –11 ). Their structures including absolute configurations were elucidated by multi-spectroscopic data analyses, chemical methods, and quantum chemical ECD calculations. The compounds (1 –11 ) were tested for their antioxidant activity using 2, 2-diphenyl-1-picrylhydrazyl (DPPH), 2, 2′-azino-bis (3-ethylbenzothiazoline-6-sulphonicacid) (ABTS) and Ferric reducing antioxidant power (FRAP) assays. All the isolated compounds displayed different degrees of antioxidant effects. Meanwhile, some isolates also possessed acetylcholinesterase (AChE) inhibitory activities. A possible mechanism of interaction between the active compounds and AChE was also investigated by molecular docking studies. Furthermore, compounds (1 –6 and10 –11 ) exhibited potent neuroprotective effects against H2 O2 -induced cellular damage in human neuroblastoma SH-SY5Y cells.